The Future of LNG in Indonesia, Opportunity Analysis of Mini LNG Plant - Murdani, Agung; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract.The demand for oil in the world shows significant growth and it makes world oil reserves are being reduced time after time. Even though, there are increasing in world oil reserves, but the gap between world total oil consumption and world total oil production makes those increasing oil reserves become meaningless. There are growth in domestic energy demand and create imbalance of energy supply in Indonesia, like energy supply shortage that occurred in North Sumatra, causing the electricity crisis in Medan city and its surrounding areas. With the high price of diesel that used as an energy source for the generator at PLN also in medium and large industries, gas became one of the cheap new energy to replace oil-based energy. The purpose of this journal is to analyze the opportunity of mini LNG plant in Indonesia through maximizing gas potential by doing internal and external factors analysis that can affect the development of mini LNG plant and the future of LNG in Indonesia. So not only Indonesia will have national competitive advantage but also help the future of LNG in Indonesia. To get deeper understanding of information and focus on the issue about LNG, author used qualitative methodology or qualitative data collection. The advantage of this method is its capability to provide complex descriptions of people experiences that related to specific issue. This is generally done in interviews, open-ended questions, or focus groups. Even though LNG is a risky business but there was many example of mini LNG plant that success in the world like in Australia, Brazil, China, and USA. One similarity is all the mini LNG plant aimed to meet domestic energy demand. To ensure that mini LNG plant will become profitable there are several factors must be consider like location to build it, partners to collaborate, carefully in preparing financial plan, choosing right equipment and technology also employees. To make local companies more competitive, when building LNG infrastructure every LNG business players should focusing to buy materials from the local vendor or companies and reduce the dependency on foreign vendors. Risk in LNG plant can be reduce by giving right SOP or guidance, training or specialized training for the employee and have a good human resource management.Keyword: world oil reserves, LNG, mini LNG plant, national competitive advantage, future of LNG in Indonesia.Â